Outcome Measures in UCLP: The Modified 5-Year-Olds'-Index—Development and Reliability. (February 2019) - Mittal, Tarun K.; Ireland, Anthony J.; Atack, Nikki E.; Leary, Sam D.; Russell, Joyce I.; Deacon, Scott A.; Ness, Andy R.; Sandy, Jonathan R.
Objective: Can we reliably discriminate severity within the existing categories of the 5-Year-Olds' Index? Design: Retrospective method comparison and development study. Setting: School of Oral and Dental Science, University of Bristol. Methods: Dental study models of 5-year-olds with unilateral cleft lip and palate (UCLP) were collected from the archives of 2 national cleft surveys (n = 351). One hundred randomly selected models were ranked to construct the modified 5-Year-Olds' Index and also scored using a visual analogue scale (VAS). Reliability testing was performed on 51 study models. Visual analogue scale scores were used to aid statistical analysis and investigate the reliability of a VAS for outcome measurement. The modified 5-Year-Olds' Index was then applied to 198 study models of 5-year-olds with UCLP. Results: The modified 5-Year-Olds' Index showed excellent intra and interexaminer agreement (intraclass correlation > 0.94) and good discrimination of severity. When applied to the Cleft Care UK participants (n = 198), the modified 5-Year-Olds' Index showed good discrimination of severity within the better categories (groups 1-3) of the 5-Year-Olds' Index. Visual analogue Scale scores resulted in unacceptable variation between measurements. Conclusions: The new modified 5-Year-Olds' Index is a reliable method of assessing outcomes at 5 years of age and showed improved discriminatory power between the "better" outcome categories than the original 5-Year-Olds' Index. A VAS was found to be unsuitable for assessing outcome at 5 years of age for children with UCLP.